Who Goes East? The Impact of Enlargement on the Patterns of German FDI - Claudia M. Buch; Jörn Kleinert (Institut für Angewandte Wirtschaftsforschung (IAW), 2006)
Affiliates of German firms in Eastern Europe differ from those in the rest of the world. They have smaller sales and they employ more labor. Labor productivity is thus lower than in affiliates of German firms elsewhere. Moreover, multinational activity in Eastern Europe is mostly unilaterally whereas, for industrialized countries, bilateral FDI linkages dominate. In this paper, we aim at explaining differences in the activities of German multinational firms in Eastern and Western Europe. Do German firms engage in different activities in Eastern and Western Europe, i.e. do the types of affiliates differ? Or do smaller German parent firms particularly benefit from enlargement, i.e. do characteristics of the parents differ in a systematic way?
Keywords: F15; L23; F23; 330; Eastern enlargement; foreign direct investment; firm heterogeneity